The relationship between emotional eating behavior and psychoemotional state of patients with gastroenterological diseases under the influence of wartime factors in Ukraine - L.V. Demeshkina (Gastroenterologìa, 2025)
Background. Russia-Ukraine war is powerful stressor trigger that can lead to psychological disorders (e.g., depression, anxiety) in Ukrainian population. It is known that war and stress can also change people’s eating habits. The purpose was to study the relationship between the level of depression and anxiety and emotional eating behavior in patients with gastroenterological diseases under the influence of wartime factors. Materials and methods. Hospital Anxiety and Depression Scale (HADS), and Dutch Eating Behavior Questionnaire were used. HADS (both depression and anxiety) scores ≥ 8 and ≥ 11, respectively, indicated borderline abnormal and abnormal disorders, respectively. Body mass index (weight/height2) was calculated as well. Results. Forty patients with different gastroenterological diseases were included in this study. A mandatory condition for patients’ inclusion was their living in Ukraine from the beginning of Russian aggression until hospital admission. The mean age of the participants was (37.53 ± 1.59) years, range was 18–52 years, and most of them were male (70.0 %). There are changes in some indices of psychosocial status in 45.0 % of patients. Anxious and depressive changes (borderline abnormal and abnormal) were revealed in 42.5 and 17.5 % of patients, correspondingly, and 15.0 % of patients had their combination. The emotional eating behavior was diagnosed in 32.5 % of the examined patients, and it positively correlated with the level of anxiety and depression (r = 0.38, p = 0.015 and r = 0.34, p = 0.03, respectively), and negatively correlated with age (r = –0.51, p = 0.001). Conclusions. More than a third of patients with gastroenterological diseases had abnormal anxiety or depression during Russia-Ukraine war. Strong positive correlation was found between anxiety, depression and emotional eating behavior. Further research is needed to evaluate the overall impact of the war on health of Ukrainian people, including their psychosocial status. The rehabilitation intervention, special medical programs, and international help are needed for Ukrainian population to overcome war consequences that influenced people health.